Highly Cross-Linked vs Conventional Polyethylene: No Differences in Rim Notching From Micromotion on Retrieved Acetabular Liners - Paterson, Nicholas R.; Teeter, Matthew G.; MacDonald, Steven J.; McCalden, Richard W.; Howard, James L.; Naudie, Douglas D.R. (The Journal of arthroplasty, 2012)
Previous literature suggested highly cross-linked acetabular liners demonstrated notching patterns that may be a point of crack origin and rim failure. We examined (1) whether notching patterns and rim cracks existed and demonstrated similar morphological properties in retrieved highly cross-linked and non–cross-linked liners and (2) whether the dimensions of these notches correlated with their duration of implantation. We retrieved a series of 14 identical liners out to an average of 2.03 years. Liners were microscopically examined and then scanned using microcomputed tomography. All liners demonstrated identical notching patterns. Microcomputed tomographic scans demonstrated no signs of crack initiation or rim failure but were able to accurately quantify the notch dimensions. The notching patterns were likely caused by liner-cup micromotion and are better characterized as creep deformation because they did not progress markedly over longer durations of implantation.